MICROBIOLOGY AND PHYSICOCHEMICAL PROPERTIES OF MECHANIC WORKSHOP POLLUTED SOIL AMENDED WITH COWPEA CHAFF IN ANYINGBA, KOGI STATE, NIGERIA - E., Stephen; B.E, Ekwetafia; E.E., Esemikose; E.A.2, Akogu; O.P, Abioye (Malaysian Journal of Science, 2013)
The microbiological and physicochemical properties of mechanic workshop polluted soil amended with 5.6 % (w/w) cowpea chaff were studied for a period of eight weeks. The results revealed an appreciable increase in the microbial population of the mechanic workshop polluted soil amended with cowpea chaff (MPSA) than unamended mechanic workshop polluted soil (MPS). The bacteria counts ranged from 3.0 x106 cfu/g to14.0 x106 cfu/g for MPS, 3.0 x 106 cfu/g - 48.0 x106 cfu/g for MPSA and 3.0 x 106 cfu/g - 22.0 x106 cfu/g for oil free soil (OFS) while the fungi counts ranged from 8.0 x 106 cfu/g to 15.0 x106 cfu/g for MPS, 8.0 x 106 cfu/g -22.0 x 106 cfu/g for MPSA and 2.0 x 106 cfu/g – 21.0 x106 cfu/g for OFS. There were significant differences at 5% probability levels in both bacteria and fungi counts. Higher pH, moisture contents, electrical conductivity and phosphorus concentration were observed in MPSA compared to MPS and OFS. Significant differences exist in the pH, moisture contents and nitrogen concentration at 5% probability levels. However, no significant differences (p>0.05) were observed in the electrical conductivity, phosphorus, organic carbon and organic matter contents of the soils. The results suggest that cowpea chaff could be used as biostimulating agent in reclaiming mechanic workshop polluted soil. (Keywords: mechanic workshop polluted soil, cowpea chaff, biostimulating agent, physicochemical properties)